DISTRIBUTION AND ISOLATION OF Bacillus thuringiensis IN COLOMBIA - DÍAZ, THAIS; RESTREPO, NORA; ORDUZ, SERGIO; ROJAS, WILLIAM (Revista Colombiana de Entomología, 1993)
ln order to find natural enemies of mosquitoes, entomopathogenic bacteria were isolated from soil and dead mosquito larvae samples taken from different areas in the country. The methodology of Brownbridge and Margali for the isolation of spore-forming bacteria was used. The isolates showing toxicity towards Culex quienquefasciatus (Say) larvae were submitted to tests of biochemical identification and sensibility to antibiotics. Using larvae of C. quinquefasciatus, Aedes aegypti (L.) and Anopheles stephensi Liston the LC50 was determined. A total of 79 isolates of Bacillus thuringiensis Berliner toxic to mosquito larvae were found. The isolates CIB 163-131 and CIB 24-273 were found to belong to the serotype H-30,.new for the world, and it was nominated Bacillus thuringiensis subsp. medellin (B.t.m.). The toxic proteins of those isolates showed immunological characteristics different from those of B. thuringiensis subsp. israelensis, which is well distributed in the tropical warm areas of Colombia.